Economic Ground of Efficiency of Publicity Campaign Экономическое обоснование эффективности рекламной кампании - Agarkova Anna A. (Bìznes Inform, 2012)
The methods of measuring of efficiency of publicity campaign of enterprise are examined in the article, and also problems are related to the legal adjusting of publicity activity in Ukraine. Basic difficulties are selected in connection with the use each of methods of determination of efficiency of publicity campaign. Basic indexes which characterize efficiency of publicity campaign are exposed in the article. Incentive reasons, which compel a potential buyer with kindness to react on what an advertiser wants to obtain, are examined. В статье рассматриваются методы измерения эффективности рекламной кампании предприятия, а также проблемы связанные с правовым регулированием рекламной деятельности в Украине. Выделяются основные трудности в связи с использованием каждого из методов определения эффективности рекламной кампании. В статье указанны и раскрыты основные показатели, которые характеризуют эффективность рекламной кампании. Рассматриваются побудительные мотивы, которые заставляют потенциального покупателя благожелательно реагировать на то, чего хочет добиться рекламодатель.